2011
DOI: 10.1002/stem.740
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Melanocytes to Neural Crest Stem-Like Cells by One Defined Factor

Abstract: Mouse and human somatic cells can either be reprogrammed to a pluripotent state or converted to another lineage with a combination of transcription factors suggesting that lineage commitment is a reversible process. Here we show that only one factor, the active intracellular form of Notch1, is sufficient to convert mature pigmented epidermal-derived melanocytes into functional multipotent neural crest stem-like cells. These induced neural crest stem cells (iNCSCs) proliferate as spheres under stem cell media c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 53 publications
1
44
0
1
Order By: Relevance
“…In line with this finding, NICD1 has been shown to directly regulate other neural-crest-and Notch-related processes. The overexpression of NICD1 alone is sufficient to convert melanocytes into neural crest stem-like cells (Zabierowski et al, 2011), and NICD1 interacts with b-catenin to upregulate Notch target genes (Jin et al, 2009). Thirdly, the inhibition of Notch signaling during neural crest induction, either by treatment with DAPT or by silencing JAG1, suppressed neural-crest-specifier gene expression and caused the cells to switch their fate towards a neural identity.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, NICD1 has been shown to directly regulate other neural-crest-and Notch-related processes. The overexpression of NICD1 alone is sufficient to convert melanocytes into neural crest stem-like cells (Zabierowski et al, 2011), and NICD1 interacts with b-catenin to upregulate Notch target genes (Jin et al, 2009). Thirdly, the inhibition of Notch signaling during neural crest induction, either by treatment with DAPT or by silencing JAG1, suppressed neural-crest-specifier gene expression and caused the cells to switch their fate towards a neural identity.…”
Section: Discussionmentioning
confidence: 99%
“…This may be in part due to the post-mitotic state of the target cell type (neuronlike cells), with the conversion procedure including a halt in proliferation, thus limiting the ability of these cells to expand once reprogrammed [98][99][100] . In addition to determining methods of increasing conversion efficiency, studies have expanded into investigating whether similar methods could be utilised for generation of proliferative neural stem and progenitor cells, which are both expandable in vitro and capable of generating multiple neural cell types [101] , with initial studies demonstrating the generation of induced neural progenitor [101] and crest [102] cells. Kim et al [101] first demonstrated the direct conversion of mouse embryonic fibroblasts into induced neural progenitor cells, through transient expression of the iPSC reprogramming factors Oct4, Sox2, Klf4, and cMyc, followed by incubation in a defined neural repro gramming media.…”
Section: Generation Of Induced Neural Stem and Progenitor Cellsmentioning
confidence: 99%
“…Developments in protocols for direct reprogramming of patients' cells into cardiomyocytes have potentially high clinical significance [44,45]. Direct reprogramming was successfully accomplished in other types of cells, with neurons and neuron-related cells obtained through transdifferentiation of Sertoli cells [46], melanocytes [47] and fibroblasts [48,49].…”
Section: Cell-fate Reprogramming Through Gene Transfer For the Needs mentioning
confidence: 99%